Atopic dermatitis in Ethiopian children: a multicenter study of clinical severity, characteristics, and sociodemographic factors - Kelbore, Abraham Getachew; Enbiale, Wendemagegn; van Wyk, Jacqueline M.; Mosam, Anisa (Frontiers in Medicine, 2024)
Background Atopic dermatitis (AD) is a chronic relapsing, pruritic, inflammatory skin disease. Assessing the characteristics and risk factors of severe AD is central to healthcare workers’ understanding and subsequent education of patients for the most optimal outcomes. The clinical characteristics are known to vary depending on populations and regions. AD has been well-documented in the global North in mainly Caucasian populations, while very few studies have been conducted on African patients residing in Africa. This study assessed the clinical characteristics, severity, and sociodemographic factors of children with AD in Southern Ethiopia. Methods A hospital-based cross-sectional study was conducted among 461 children and their caregivers in four randomly selected hospitals in Southern Ethiopia from October 2022 to September 2023. A systematic sampling technique was used to enroll study participants. Clinical profile and sociodemographic data were collected by trained data collectors. The Scoring Atopic Dermatitis (SCORAD) index tool was used. The descriptive analysis was performed to characterize study participants. Univariate and ordinary logistic regression were used to identify factors associated with the SCORAD index score. The OR with 95% was used to show the strength of association, and a p-value of <0.05 was used to declare the level of significance. Result Out of 461 AD-diagnosed children, 212 (46%) were girls and 249 (54%) were boys. In the sample of pediatric patients, 149 (32.3%) exhibited mild AD, 231 (46.2%) presented with moderate, and 99 (21.5%) showed signs and symptoms of severe AD. All patients had itching. Dryness of skin, excoriation, and erythema, followed by lichenification, were the most observed signs. In the ordinary logistic regression model, age onset of the disease [AOR 95% CI 1.95 (1.3–2.94)], sex of caregiver or family [AOR 95% CI 0.61 (0.41–0.90)], family atopy history [AOR 95% CI 0.64 (0.44–0.93)], mother education status [95% CI 2.45 (1.1–5.47)], and use of herbal medication [AOR 95% CI 0.50 (0.33–0.79)] were significantly associated with the severity of AD. Conclusion In this study, 68% of children were found to have moderate-to-severe AD. Early onset, maternal education, familial atopy history, sex of caregiver, and use of herbal medication were independent predictors of severe AD in children. We recommend further investigation into these variables for their potential to serve as markers to assess the severity of AD and improve the care and management of children with AD in Ethiopia.